Influence Of Product Reviews on User Satisfaction of the Female Daily Application - Amienah Atthahirah (Jurnal Manajemen Bisnis Eka Prasetya, 2023)
Product reviews currently have an important role in knowing new information and becoming a consideration that will later become a purchasing decision. Many platforms accommodate a collection of information about product information as a potential fulfillment of user expectations. Is the product review able to fulfill user Female Daily Application's expectations? The purpose of this study is to determine whether product reviews have an influence on user satisfaction of the Female Daily application. The reasearch method used is a quantitative and data processing using SPSS version 27.0. The results showed that there was a strong influence between product reviews on user satisfaction as evidenced by the results of the determination coefficient test of 72.9% of the Female Daily application user satisfaction was determined by product reviews, while the remaining 27.1% was determined by other things outside this study.